Identifikasi Methanil Yellow Pada Jamu Tradisional yang Dijual Di Pasar Karuwisi Kota Makassar - Andi Indrawati; Mutmainnah Mutmainnah (Jurnal Media Laboran, 2020)
Jamu is a term for traditional medicine from the Java region. Jamu is also known as medical medicine, herbal medicine, herbiology, and herblore. The benefits of herbal medicine itself, depending on the type of herbs used for treatment. Herbal medicine is made from natural ingredients, in the form of parts of plants such as rhizomes (roots), leaves and bark, fruit. There is also use of materials from animal bodies, such as goat bile or crocodile tangkur. Herbal medicine usually tastes bitter so it is necessary to add honey as a sweetener so that the taste is more tolerable to the drinker. Methanil Yellow is a synthetic dye used in the textile industry. Misuse of Methanil Yellow includes noodles, crackers, and other snacks that have a striking yellow color. Methanil Yellow dye is very dangerous if inhaled, in contact with the skin, in contact with the eyes, and swallowed. Methanil Yellow is a synthetic dye that is prohibited for food products because it contains heavy metal residues which are very harmful to health. The results of the Methanil Yellow research on the traditional herbal medicine showed that the herbs that had been tested did not contain Methanil Yellow or were negative. By looking at the results of research that has been carried out on the 5 samples studied, it can be seen that the five samples are NEGATIVE.